2017
DOI: 10.1016/j.spasta.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Modelling spatio-temporal data with multiple seasonalities: TheNO2Portuguese case

Abstract: a b s t r a c tThis study aims at characterizing the spatial and temporal dynamics of spatio-temporal data sets, characterized by high resolution in the temporal dimension which are becoming the norm rather than the exception in many application areas, namely environmental modelling. In particular, air pollution data, such as NO 2 concentration levels, often incorporate also multiple recurring patterns in time imposed by social habits, anthropogenic activities and meteorological conditions. A two-stage modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The rainfall distribution in the state of Paraíba showed a clear correlation for both space and time, thereby justifying the use of spatiotemporal kriging. When constructing the spatiotemporal variogram of the residues, several researchers found that spatial dependence became weaker with an increase in time, while the temporal dependence became insignificant over vast spatial distances [19,21,27,33]. In the studies mentioned above, the modeled phenomena did not present common characteristics in the spatiotemporal structure during the construction of the variogram.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The rainfall distribution in the state of Paraíba showed a clear correlation for both space and time, thereby justifying the use of spatiotemporal kriging. When constructing the spatiotemporal variogram of the residues, several researchers found that spatial dependence became weaker with an increase in time, while the temporal dependence became insignificant over vast spatial distances [19,21,27,33]. In the studies mentioned above, the modeled phenomena did not present common characteristics in the spatiotemporal structure during the construction of the variogram.…”
Section: Discussionmentioning
confidence: 97%
“…Although the covariates exhibit spatial, temporal, and spatiotemporal variations, the regression model alone cannot account for all the variations. Therefore, the residuals of this model may exhibit spatiotemporal dependencies, indicating that a spatiotemporal variogram can be estimated and later used to interpolate the residues with kriging [19].…”
Section: Components Of the Trendmentioning
confidence: 99%
“…Several studies that deal with spatial-temporal modeling and which have null values in the database have used the regression model with Normal distribution [11,32] or the Gamma regression model [12,13]. However, the Normal regression does not solve the data asymmetry problem, and the Gama regression does not contemplate in its domain the occurrence of zeroes.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have evaluated non-Gaussian models, including generalized linear models (GLM), with variable response Gamma [12,13]. Once the Gamma model is assumed, the variable domain has to be strictly positive, and it does not include the value zero.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation